Pengaruh Work Life Balance, Kepuasan Kerja, Self Efficacy dan Komitmen Organisasi Terhadap Kinerja Karyawan RSU Ananda Purwokerto - Yayan Raihan Herdiansyah; Suyoto; Hengky Widhiandono; Irawan Randikaparsa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of work life balance, job satisfaction, self efficacy, and organizational commitment on employee performance at RSU Ananda Purwokerto. This study uses a quantitative approach. The population in this study were all health workers at RSU Ananda totaling 154. The sampling technique used purposive sampling with the criteria for respondents being health workers who do not have a position or leadership and have worked for at least one year. The number of samples in this study was 111 employees. The data analysis techniques used in this study were validity testing, reliability testing, and hypothesis testing using smartPLS 4.0. The results of the study showed that the variables work life balance, job satisfaction, and self efficacy had a significant positive effect on employee performance, while the variable organizational commitment had a positive but insignificant effect. These findings are expected to be a guide for RSU Ananda management in designing and implementing strategic policies to improve employee performance optimally.